2012
DOI: 10.1016/j.visres.2012.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Challenging the distribution shift: Statically-induced direction illusion implicates differential processing of object-relative and non-object-relative motion

Abstract: The direction illusion is the phenomenal exaggeration of the angle between the drift directions, typically, of two superimposed sets of random dots. The direction illusion is commonly attributed to mutual inhibition between direction-selective cell populations (distribution-shift model). A second explanation attributes the direction illusion to the differential processing of relative and non-relative motion components (differential processing model). Our first experiment demonstrates that, as predicted by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 51 publications
0
10
1
Order By: Relevance
“…When transparent motion RDKs were presented with a static line orthogonal to the motion stimulus' nonobject-relative component velocity, the DI was negated. Conversely, a substantial illusion was found when there was no line or when the line was parallel to the nonobject-relative motion component (Farrell-Whelan et al, 2012a).…”
Section: Theoretical Accounts Of the Direction Illusionmentioning
confidence: 93%
See 4 more Smart Citations
“…When transparent motion RDKs were presented with a static line orthogonal to the motion stimulus' nonobject-relative component velocity, the DI was negated. Conversely, a substantial illusion was found when there was no line or when the line was parallel to the nonobject-relative motion component (Farrell-Whelan et al, 2012a).…”
Section: Theoretical Accounts Of the Direction Illusionmentioning
confidence: 93%
“…Further support for the differential processing model was recently provided by Farrell-Whelan et al (2012a), who found that a static line could produce a shift in the perceived direction of a single set of dots: a ''staticallyinduced direction illusion'' reminiscent of the ''slalom effect'' (Cesàro & Agostini, 1998;Ito & Yang, 2013). A static line with endpoints that are obscured provides no positional reference cues for moving objects along the axis of its orientation (Farrell-Whelan et al, 2012a).…”
Section: Theoretical Accounts Of the Direction Illusionmentioning
confidence: 95%
See 3 more Smart Citations